1997
DOI: 10.1046/j.1365-2141.1997.3703182.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinaemia in heterozygous β‐thalassaemia is related to co‐inherited Gilbert's syndrome

Abstract: The reasons why heterozygotes for β‐thalassaemia have considerable variation in serum bilirubin levels are unkown. High levels of bilirubin could be related to the co‐inherited Gilbert's syndrome, determined either by mutations of the coding region or by variation in the A(TA)nTAA motif of the promoter of the bilirubin UDP‐glucuronosyltransferase gene (UGT‐1). We sequenced the coding and the promoter region of UGT‐1A or characterized the A(TA)nTAA motif of the promoter by denaturing gel electrophoresis of radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
40
2
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 10 publications
5
40
2
2
Order By: Relevance
“…These findings suggested that the prevalence of the (ta) 7 mutation might be low among people of African origin. However, we now report that contrary to expectation, the (ta) 7 form is more common among people of African origin than among Caucasians. Although Asians seem to have higher bilirubin levels than whites, the (ta) 7 is much less common in that population.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…These findings suggested that the prevalence of the (ta) 7 mutation might be low among people of African origin. However, we now report that contrary to expectation, the (ta) 7 form is more common among people of African origin than among Caucasians. Although Asians seem to have higher bilirubin levels than whites, the (ta) 7 is much less common in that population.…”
contrasting
confidence: 99%
“…However, we now report that contrary to expectation, the (ta) 7 form is more common among people of African origin than among Caucasians. Although Asians seem to have higher bilirubin levels than whites, the (ta) 7 is much less common in that population. Among Africans not only the (ta) 6 and (ta) 7 forms are found, but there are also promoters that contain five or eight ta repeats [(ta) 5 and (ta) 8 ].…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…in b-thalassaemia (Galanello et al 1997(Galanello et al , 1999b, G6PD deficiency (Galanello et al 1999a) and SCD (Adekile et al 2005;Chaar et al 2005;Fertrin et al 2003;Harverfield et al 2005;Passon et al 2001). In fact, in addition to the results presented here, the mentioned studies performed in SCD (Table 1).…”
Section: Discussionsupporting
confidence: 63%
“…This predicted value is higher than that of patients with a clinical diagnosis of Gilbert syndrome, reflecting the existence of other inherited or acquired factors affecting bilirubin metabolism, in addition to reduced glucuronidation caused by the (TA) insertion. The awareness that the (TA) insertion is the most frequent cause of Gilbert syndrome prompted the study of its association with other pathologies, namely h-thalassemia [22,23], sickle cell anemia [24], ABO incompatibility [25], glucose-6-phosphate dehydrogenase deficiency [26 -28], hereditary spherocytosis [29,30,31] and neonatal icterus [32,33].…”
Section: Discussionmentioning
confidence: 99%